Numerical Studies of Floor Heave Control in Deep Mining Roadways with Soft Rocks by the Rock Bolts Reinforcement Technology - Ivan Sakhno; Svitlana Sakhno (Advances in Civil Engineering)
The floor heave is one of the key factors that can restrict high-efficiency and safety mining, especially in the deep roadways with soft rock. Considering the influences of rock fracturing over time on rock mass properties, a case study of the floor heave evolution and rock bolts reinforcement technology was performed in this paper. A numerical simulation was used to study the stress-strain state and displacement of surrounding rocks. It was found that significant floor heave caused by nonlinear deformation of laminated immediate floor under an increase in rock fracturing. The post-peak strain regions appear in the bottom corners of the roadway, after which strata in the immediate floor are destroyed one by one. The joint spacing of 0.45 m on the immediate floor is critical. At this step, post-peak strain regions merge in the central part of the roadway floor, which is the cause of uncontrolled floor heave. Rock bolts reinforcement was proposed to control the floor heave. Three floor support schemes with two types of support elements, different bolt orientations, and lengths of reinforcement were studied. The numerical simulation demonstrated that after reinforcement, post-peak plastic strain in the floor strata was reduced effectively. The optimal floor support scheme and depth of reinforcement were determined by the allowable floor heave. Ideally, the floor heaves could be reduced by rock bolts with a steel belt installed according to the support scheme III and reinforcement length of 2.0 m for outer bolts and 3.0 m for central bolts.